The public welfare dimension of the competition clauses an exposition and application of the proper constitutional treatment for industries with adverse public health impacts (2017)
This Article presents a systematic exposition of the competition clauses under Section 19, Article XII of the 1987 Philippine Constitution, as well as adjunct antitrust provisions under paragraph 2. Section 1, Article XII and Section 11(1), Article XVI. The analysis ultimately reframes the competition clauses as a cognate of (1) pro- competition policy as commonly articulated in restraint of trade jurisprudence and (2) the public welfare. This Article, properly situates and highlights public welfare or the "common good" as a discrete element-—a construction hitherto unpronounced in Philippine legal literature. With this normative background, this Article then demonstrates how an imposition of a two-tier taxation structure for tobacco products or similar excise tax regimes results in a violation of the competition clauses. In particular, the Article argues that the enactment of H. No. 4144, a highly popular measure, which passed in the House of Representatives in December 2016, would establish and institutionalize an unreasonable restraint of trade from the perspective of both elements. In addition, this Article examines extensive domestic jurisprudence on restraint of trade, synthesizing these to propound anti-competition controversies under the following typology: contractual, statutory; and constitutional. In this manner, too, the public welfare dimension of the competition clauses is made more explicit for the purposes of future litigation.however
Keywords: Public welfare; Tobacco -- Taxation; Tobacco industry -- Taxation; Competition policy